2004
DOI: 10.1046/j.1365-2516.2003.00840.x
|View full text |Cite
|
Sign up to set email alerts
|

Central venous access devices in haemophilia

Abstract: Central venous access devices (CVADs) can facilitate repeated and/or urgent administration of coagulation factors in haemophilic patients. We conducted a systematic review and meta-analysis of complication rates and risk factors for poor outcome. Forty-eight studies with a total of 2704 patients and 2973 CVADs were included. The primary indications for CVADs were immune tolerance therapy (34.9% of patients), difficult venous access (31.8%) and prophylaxis (29.1%). Fully implanted CVADs were employed in 77.4% o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
183
3
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(199 citation statements)
references
References 64 publications
(251 reference statements)
11
183
3
2
Order By: Relevance
“…Invasive procedures during the antenatal/perinatal period and FVIII infusions during vaccinations or infections were evaluated for the first time in our series, showing no role on inhibitor development. Since catheter-related infections were included in the analysis, our results indirectly suggest that infections associated with the use of central venous catheters in haemophilic children (Valentino et al, 2004) are not associated with a higher inhibitor risk. FVIII treatment for severe bleeding or surgery has been suspected to influence inhibitor formation because extensive tissue damage and inflammation may trigger an antibody response against extravascular FVIII (Oldenburg et al, 2004).…”
Section: Discussionmentioning
confidence: 87%
“…Invasive procedures during the antenatal/perinatal period and FVIII infusions during vaccinations or infections were evaluated for the first time in our series, showing no role on inhibitor development. Since catheter-related infections were included in the analysis, our results indirectly suggest that infections associated with the use of central venous catheters in haemophilic children (Valentino et al, 2004) are not associated with a higher inhibitor risk. FVIII treatment for severe bleeding or surgery has been suspected to influence inhibitor formation because extensive tissue damage and inflammation may trigger an antibody response against extravascular FVIII (Oldenburg et al, 2004).…”
Section: Discussionmentioning
confidence: 87%
“…Infections represent the major complication associated with CVAD use in haemophilia and the most common cause for their removal, with higher risk for external devices than subcutaneous ports (Ljung, 2007). This complication is more frequent in inhibitor patients (van Dijk et al, 2004;Valentino et al, 2004;Mancuso et al, 2008). A preliminary report from the I-ITI study showed that CVAD infections occurred frequently during ITI.…”
Section: Infections and Immunological Challengesmentioning
confidence: 99%
“…However, some studies have shown a much higher frequency of infections, 1-2/ 1000 catheter-days [54,55]. In a meta-analysis of 48 studies with 2704 patients and 2973 central venous access devices (of which only 77% were implanted), the average frequency of infection was 0.66 per 1000 catheter-days [56]. It is well known that implantable devices, such as the Port-A-Cath, have a lower infection rate compared with that of external catheters.…”
Section: Central Venous Lines -Why Such Diverse Experiences?mentioning
confidence: 99%